Eficiência da higienização e de ação detergente enzimático em comparação ao alcalino clorado em abatedouro de aves - Flores, Aline Fatima (2015)
The quality of food is directly linked to production hygiene and especially of contact surfaces during the production process, which can become sources of contamination when poorly sanitized. To evaluate the cleaning efficiency in a poultry slaughterhouse, were performed ATP-bioluminescence test to evaluate the presence of all organic matter on the surfaces before and after cleaning. It was also tested the efficiency of enzymatic detergent in comparison to chlorinated alkaline detergent in the cleaning process on polypropylene cutting boards used in the industry, by standard plate count for total aerobic mesophilic. All surfaces were found to be on alert or in unacceptable conditions, ie all results were above 2.18 log URL. All results obtained significant difference at the level of 5% probability by Tukey's test, assuming that there is a considerable decline in organic matter on surfaces after cleaning. By comparing the detergents, there was no significant difference, being considered similar in its scope, but none achieved satisfactory results in the total mesophilic count.